Akselerasi Kapasitas dan Daya Saing UMKM Keripik Singkong melalui Pendampingan Digital Branding dan Pemanfaatan E-Commerce - Sunari Sunari; Vania Zerlinda; Badrus Salam; Wahyu Dwi Antikasari; Yora Surya; Yuda Alviansah; M. Edi Purnomo; Ardiansyah Ardiansyah; Ismi Nur Hidayah; Tarisa Aura; Revinda Nurvianisa; Ananda Rachmatia; M. Adi Nurul; Laila Sulistya; Zahwa Dwi; Lailul Mukarromah; M. Habib; Lailatur Roikhatus; Elien Devrina; M. Alvin; Alifia Putri; Dea Dwi; Mia Eli Sabet; Hestin Yanda; Alfira Ragita; Maulia Nur; David Handy (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
In response to the rapid development of technology in the economic sector, every Micro, Small, and Medium Enterprise (MSME) is required to accelerate its competitive capacity. The Community Service Program (Kuliah Kerja Nyata/KKN) plays a role as a form of community engagement aimed at empowering local potential, including Micro, Small, and Medium Enterprises (MSMEs). Several challenges faced by the cassava chips MSME at the KKN location include low business capacity and competitiveness due to limited branding and minimal utilization of digital marketing technology.The objective of this community service activity is to accelerate the capacity and competitiveness of the cassava chips MSME through digital branding assistance and the utilization of digital marketplaces. The implementation employed observation, socialization, and direct assistance methods to MSME actors, which included the creation and updating of brand identity (logo), registering the business location on Google Maps, and mentoring in the establishment of digital stores on e-commerce platforms. The results of this activity indicate an increase in MSME actors’ understanding of the importance of branding and digital marketing, as well as an expansion of product marketing reach through online channels. This KKN activity has a positive impact on enhancing business capacity and serves as an initial step toward strengthening the sustainable competitiveness of MSMEs.